English language growth after university entry - Oliver, Rhonda; Rochecouste, J.; Mulligan, Denise (Pergamon/Elsevier, 2012)
Almost 800 international students from non-English speaking backgrounds enrolled at five Australian universities responded to an online survey accessed through a dedicated website. The survey captured demographics; language and language learning background; strategies for continuing to develop English; motivation, attitudes and beliefs about learning English; and academic learning strategies. These data were then matched with normalized measures of the participants’ academic achievement (e.g., Grade Point Averages or GPAs). Correlational analysis between students’ learning strategies for English and their academic standing was then undertaken. Additionally, students provided extensive rich qualitative data through open-ended questions and interviews. The findings of our research show that a range of language learning strategies which may be promoted in early to advanced second and foreign language learning environments in the home country may not be advantageous once entering university. In fact, our research suggests that some of these strategies may be detrimental to academic success. By contrast, risk-taking strategies appeared to favour success.